The Incidence of Chickenpox in Penal Institution of the Lipetsk Region - S. V. Provotorova (Эпидемиология и вакцинопрофилактика)
Relevance. Chickenpox is one of the most common infections in Russia and retains a stable 2–3 place in the structure of infectious morbidity. The conditions of the closed adult community in the institutions of the penal correction system pose high risks for the occurrence of group cases of Chickenpox , and this disease in adults can pose a threat to life.Aims. Incidence rate of chickenpox among convicts detained in correctional institutions of the prison system of Lipetsk region in 2009–2018.Materials & Methods. The statistical data of the branch CGSN of the Federal Penitentiary Institution MCH-48 of the Federal Penitentiary System of Russia were to analyse the incidence of chickenpox by prisons in the penitentiary system of the Lipetsk Region for the period from 2009 to 2018.The materials of the study were forms of federal state statistical observation for 2009–2018. The method of retrospective epidemiological analysis was used. statistical data processing was performed using Microsoft Excel.Results. Cases of chickenpox among adults serving sentences in places of deprivation of liberty of Lipetsk region are recorded annually. The incidence rates among prisoners are 2 times higher than among adults in the Russian Federation. Sources of infection were relatives and convicts, patients with herpes zoster. There are statistically significant differences in first-time and re-convicted morbidity (p < 0.05). More than half (73.6%) of the cases of chickenpox occur in autumn-winter. Between 2009 and 2018, group cases were recorded with 2 to 7 people involved in the epidemic process. Consequently, conditions exist in correctional facilities for the epidemic spread of chickenpox.Conclusions. In order to prevent the occurrence and development of group cases of disease, it is proposed to introduce vaccine prevention of persons who have not suffered from chickenpox in history.